2016
DOI: 10.2174/1871520616666151111115809
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid Inhibits Proliferation, Migration, Invasion of Prostate Cancer and Modulates Drug Metabolizing and Antioxidant Enzymes

Abstract: The aim of this study was to investigate the effects of plant phenolic compound tannic acid (TA) on proliferative, metastatic, invasive properties of prostate cancer (PCa) cells; PC-3 and LNCaP, as well as drug metabolizing and antioxidant enzymes. Characterization of TA was done by using FT-IR and NMR. TA dose dependently inhibited the proliferation of PC-3 and LNCaP cells with IC50 values 35.3 μM and 29.1 μM, respectively. Wound healing assay showed that TA significantly inhibited (92.7%) migration of PCa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…In addition to metabolism and the PLA2 family, several other signaling pathways and gene families were found to be closely associated with RBM3 regulation in the present study; for example, GNG5 and the G protein pathway (26), EDN1 and the angiogenesis pathway (27), NOS3 and the NO synthesis pathway (28), CD38 and the signal transduction pathway (29), and CYP2B6 and the response to drug pathway (30). These pathways have all been reported to be important for cancer development.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to metabolism and the PLA2 family, several other signaling pathways and gene families were found to be closely associated with RBM3 regulation in the present study; for example, GNG5 and the G protein pathway (26), EDN1 and the angiogenesis pathway (27), NOS3 and the NO synthesis pathway (28), CD38 and the signal transduction pathway (29), and CYP2B6 and the response to drug pathway (30). These pathways have all been reported to be important for cancer development.…”
Section: Discussionsupporting
confidence: 52%
“…Flavonoids in dietary foods were shown to be effective in the induction of many phase II enzymes, including GPx, GSTs and NQO1 [50,51]. The importance of GST in chemical carcinogen inactivation was reported in a study on mice deficient in transcription factor Nrf2, which is required for Phase II enzyme induction [52].…”
Section: Discussionmentioning
confidence: 99%
“…Tannic acid (TA) is a prominent member of tannins family and is comprised of gallic acid molecules esterified to several functional hydroxyl groups 22 . TA exhibits potential anticancer activity against several cancer cell lines [23][24][25] . In our previous study, we demonstrated the mechanistic anticancer role of TA in prostate cancer.…”
mentioning
confidence: 99%